Occupational safety and health: the study on ergonomics at workstation in a learning institution at Klang Valley / Noor Azzura Mohamed, Khalilah Ibrahim and Mohammad Bastyian Mahmud - Mohamed, Noor Azzura; Ibrahim, Khalilah; Mahmud, Mohammad Bastyian (2011)
Occupational Safety and Health Act 1994 (OSHA 1994) has stated that working environn1ent should be conducive and comfortable to meet the physiology and psychology needs of the staff. The numbers of occupational accidents and diseases are reported to be consistently high and increasing due to the lack of attention given to ergonomics aspects in the workplace. Ergonomics should be seen as an opportunity to develop productivity and quality while escalating employees' safety, health and morale. Benefits of ergonomics are boost the productivity, enhance the quality, reduce employee injury, greater job satisfaction, increase morale, lessen medical and insurance costs, lower absenteeism, reduce lost time, decrease employee turnover and many more. The n1ain purpose of this study is to deter nine the compatibility of ergonomics in workplace environment at one of the learning institution located in Klang Valley from the employees' perception. Besides, this study also determines the relationship between ergonomics aspects with occupational disease in workplace. This study focuses on five dimensions of ergonomics, which includes working environment, welfare and facility for employees, electrical wiring, ergonomics in workstation and work organization. Meanwhile, the occupational disease at the workplace is considered, as physical disease comprises back pain, spinal pain, muscle cramps, watery eye and so on. In collecting data for this study, the researcher have used questionnaire as the main method. The data were analysed using, frequency, percentage, mean and correlation. Overall, the finding shows that the employees' perceived the compatibility of ergonomics based on five dimensions of ergonomic at the moderate to high level. In summary, the finding also shows that there is a negative and significant relation between ergonoll1ics in the workplace environment with the occupational disease.